Implementasi Metode Targhib dan Tarhib dalam Pembelajaran Akidah Akhlak Peserta Didik Mts Hidayatus Syubban Karangroto Genuk Semarang - Sudarto, Sudarto (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2017)
Child education with a method of awarding and punishing a lot is underestimated by educators, because it is so commonplace to do so. So that the existing provisions and rules are forgotten even many do not realize that the things that are considered trivial have rules. In fact, mistakes when applying this method of education, can have fatal consequences that damage the personality of the child who had previously been well formed. To get the data needed in this study, the author uses a type of field research research. The point is direct research in the field, namely in MTs Hidayatus Syubban Karangroto Genuk Semarang using a qualitative descriptive approach, the collected data is described in the form of descriptive sentences. In this writing, the aspect of research is the implementation of the Targhib and Tarhib methods in the Akidah Akhlak learning including: Giving Targhib and Tarhib, Types of Targhib and Tarhib Methods, Steps of the Targhib and Tarhib Methods. The research subject in question is someone who is used as a source to obtain research data. In this study the data collected using several methods include: Observation, Interview. From the results of the study, regarding the Implementation of Targhib and Tarhib Methods in Akidah Akhlak Learning at MTs Hidayatus Syubban Karangroto Genuk Semarang, the teacher had implemented an educational tool in the form of Targhib and Tarhib according to existing theories. In learning akidah akhlak, the rewards given to students are not in the form of valuable objects, but in the form of speeches, beautiful praise and deeds. The application of the punishment given by the teacher to students aims so that students know their mistakes and can change them and will not repeat the mistakes they have made. Teachers in giving punishment to students must be careful, because the consequences of punishment are far greater than those caused by rewards